Grammatology and Graphemics - Gelb, Ignace J. (1968)
1. Writing as a System of Signs. 2. Subdivisions of Writing. 3. Semiotics. 4. Fields of Study of Writing. 5. Grammatology. 6. Approaches to Grammatology. 7. Subdivisions of Grammatology. 8. Philology and Linguistics. 9. Writing in Relation to Language.